2010
DOI: 10.3109/14767058.2010.501156
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of neonatal drugs on the kidney

Abstract: Several drugs have been shown to produce an adverse affect on kidneys, mainly when exposure occurred during active nephrogenesis (pregnancy or prematurity). Several experimental studies on drug-related renal injury have been done on animal models. Observational reports on early drug-related nephrotoxicity in humans are increasing. The investigations regard nephrotoxicity from antibiotics (particularly aminoglycosides), angiotensin-converting enzyme (ACE) inhibitors, non-steroidal anti-inflammatory drugs and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…The identification of only a few drugs associated with AKI lends support to the hypothesis that individual medication exposure may not be as important a risk factor for AKI as multiple medication exposure. A few studies have revealed nephrotoxic medication groups such as NSAIDs, antibiotics, ACE inhibitors, chemotherapeutics, and diuretics [9,[25][26][27]. Within our study population we could find evidence that some of the above-mentioned drug groups are indeed involved in the development of AKI.…”
Section: Discussionmentioning
confidence: 73%
“…The identification of only a few drugs associated with AKI lends support to the hypothesis that individual medication exposure may not be as important a risk factor for AKI as multiple medication exposure. A few studies have revealed nephrotoxic medication groups such as NSAIDs, antibiotics, ACE inhibitors, chemotherapeutics, and diuretics [9,[25][26][27]. Within our study population we could find evidence that some of the above-mentioned drug groups are indeed involved in the development of AKI.…”
Section: Discussionmentioning
confidence: 73%
“…Despite limited studies to support its use, diuretics are commonly used to reduce ventilatory and oxygen requirements, and methylxanthines like caffeine are ubiquitous, due to the proposed beneficial short and long-term effects on respiratory and developmental status [42]. All of these can be associated with AKI with potentially long-term deleterious effects in summation [43]. …”
Section: Reviewmentioning
confidence: 99%
“…This suggests that the abnormalities may not have occurred as a result of preterm birth per se, but are likely related to factors in their postnatal care, which varied between individual neonates. For example, neonatal exposure to nephrotoxic medications (such as non-steroidal anti-inflammatory drugs and antibiotics) has been associated with both structural and functional renal injury [38]. However, a specific factor attributing to the abnormal glomeruli has not yet been established.…”
Section: The Effects Of Preterm Birth On Renal Developmentmentioning
confidence: 99%